Design and Evaluation of a Web-Based Personal Financial Management System for Young Professionals (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study design and evaluation of a web-based personal financial management system for young professionals. The system was developed to support expense tracking, budgeting, bill monitoring, savings goal management, and visual reporting through an accessible web platform. A developmental and descriptive research design was used. The prototype was built using an Agile development approach and evaluated using a software quality instrument based on functionality, usability, reliability, performance, and supportability. Twenty-seven young professionals evaluated the user-facing system, while three information technology professionals assessed technical quality. Weighted means and qualitative comments were used to interpret the results. Findings showed that the system was generally rated positively by young professional respondents, with an overall weighted mean of 3.61, interpreted as Strongly Agree. Usability received the highest mean score of 3.69, followed by reliability at 3.63, performance at 3.61, functionality at 3.60, and supportability at 3.50. IT professionals also gave favorable ratings, particularly in functionality, where the system received a mean of 4.00. The results suggest that analytics-supported features, including dashboards, category-based spending summaries, and budget alerts, can help young professionals understand their financial behavior and improve personal financial monitoring. However, the evaluation also identified areas for improvement, including clearer user guides, faster loading of reports, more consistent reminders, and possible integration with banks or e-wallets. The study contributes to applied financial technology research by demonstrating a practical prototype that combines personal finance management functions with basic data analytics for young professionals.